2005
DOI: 10.1523/jneurosci.3895-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

How Stress and Fluoxetine Modulate Serotonin 2C Receptor Pre-mRNA Editing

Abstract: In two inbred strains of mice, C57BL/6 and 129Sv, the majority of forebrain neocortical pre-mRNA encoding the serotonin 2C (5-HT 2C ) receptor is altered by adenosine-to-inosine editing. As a result, Ͼ60% of all mRNAs encode receptors with reduced constitutive and agonist-stimulated activity. However, in the BALB/c strain, a genetically distinct inbred strain with lower forebrain serotonin levels, spontaneously elevated anxiety, and increased stress reactivity, the majority of 5-HT 2C mRNA is nonedited and enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 14 publications
8
130
1
Order By: Relevance
“…In addition, it has been reported that editing of other receptors was modulated both by the genetic background and the behavioural state of the animals. 52 The reliability of our observation of increased editing is supported by the abolishment of glutamate effects on [Ca 2+ ] i , since editing of the Q/R site is known to reduce Ca 2+ permeability of GluK2. 48,53,54 Moreover, it has been reported that a mutant mouse with greatly reduced Q/R site editing showed a kainate-induced increase in [Ca 2+ ] i in cultured hippocampal neurons, whereas there was no such effect in corresponding neurons from wild-type animals.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, it has been reported that editing of other receptors was modulated both by the genetic background and the behavioural state of the animals. 52 The reliability of our observation of increased editing is supported by the abolishment of glutamate effects on [Ca 2+ ] i , since editing of the Q/R site is known to reduce Ca 2+ permeability of GluK2. 48,53,54 Moreover, it has been reported that a mutant mouse with greatly reduced Q/R site editing showed a kainate-induced increase in [Ca 2+ ] i in cultured hippocampal neurons, whereas there was no such effect in corresponding neurons from wild-type animals.…”
Section: Discussionsupporting
confidence: 52%
“…This suggests that previous studies of C57BL/6J exposed to the Forced Swim test (Englander et al 2005) may have failed to detect significant changes in editing patterns because the assays were carried out 24 hours after swimming. Certainly C57BL/6J differed from BALB/ c, which showed substantial changes, however, time frame, as well as patterns, may need to be considered.…”
Section: Discussionmentioning
confidence: 95%
“…However, there are both species-specific and brain region-specific differences in the proportions of the different variants, and only five or six variants typically are found at high frequency, with the remainder together accounting for only a few percent. Abnormalities in patterns of HTR2C editing have been reported in subsets of patients with schizophrenia and depression (Gurevich et al 2002a;Niswender et al 2001;Dracheva et al 2003), and baseline differences have also been reported among different inbred mouse strains (Englander et al 2005;Hackler et al 2006;Du et al 2006). Changes in editing patterns have been induced, in rodents, by exposure to tests of anxiety, including the forced swim test and learned helplessness, and by drugs, such as fluoxetine (Gurevich et al 2002b;Iwamoto et al 2005;Englander et al 2005;Yang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This variant results in a reduction of enzyme activity by Ϸ50% when expressed in PC12 cells. Furthermore, expression of this Tph2 variant in these inbred mouse lines is associated with reduced brain 5-HT synthesis (15) and differences in aggressive behavior (45), premRNA editing of the 5-HT 2C receptor (46), as well as responsiveness to SSRIs (47,48). However, these studies can only be viewed as correlative because they were all conducted by comparing different strains of inbred mice and the potential contribution of other genetic variations in these mice cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%